Training on Processing Cow Urine into Liquid Organic Fertilizer in Teratak Rendah Village: Pelatihan Pengolahan Urin Sapi Menjadi Pupuk Organik Cair di Desa Teratak Rendah - Seprido*, Seprido; Desriadi, Desriadi; Rizhan, Afrinald (Universitas Lancang Kuning, 2024)
Community service regarding training in processing cow urine into liquid organic fertilizer in Teratak Rendah village aims to provide direct experience to the community of Teratak rendah village in processing cor urine. This activity was carried out for 3 months and took place at the Teratak rendah villagecompost house. A total 20 participants took part in this training activity, all of them were male, 50% had elementary – Junior hight school, 60% were adults and were working productively. The raw materials for this activity use 25 liters of cow urine, 1 liter of tumeric water, 1 liter of ginger water, 4 liters of rice washing water and 4 liters of coconut water. With a total volume of 35 liters material. During the community showed a positive respons and this was proven by the many questions from participants during the activities.